Heat-conducting organic silicon composite material and electronic equipment
By adding brush-like polymers and thermal fillers of specific particle sizes to the thermally conductive silicone composite material, the problem of insufficient thermal conductivity and stability of existing materials is solved, and a silicone heat dissipation material with high thermal conductivity, low oil permeability and stability is achieved to effectively manage the heat of the optical module.
Patent Information
- Application Number
- CN202411842620.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
The existing thermally conductive silicone composite materials have shortcomings in thermal conductivity, stability and oil permeability, and cannot effectively solve the problem of thermal dissipation of optical modules.
By adding brush-like polymers to the silicone resin matrix and preparing thermally conductive fillers of specific particle sizes, a thermally conductive silicone composite material is formed to increase its yield stress and thermal conductivity while reducing oil permeability.
The silicone heat dissipation material with high thermal conductivity, stability and low oil permeability can more effectively manage the heat of the optical module and extend the service life of the equipment.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of heat dissipation technology, and in particular to a thermally conductive organic silicon composite material and an electronic device. Background Art
[0002] In the prior art, various types of optical modules have been widely developed and applied, including SFP, SFP+, QSFP, etc. However, existing optical modules still have some obvious problems in terms of transmission rate, power consumption, size and heat dissipation performance. In particular, the surge in heat causes great challenges to the performance and application of optical modules. The design of traditional heat sinks often cannot fully cope with the rapidly rising temperature. In high-power optical modules, the heat exchange capacity of the heat sink cannot quickly discharge the generated heat, resulting in a continuous rise in module temperature. Secondly, in order to achieve high integration, modern communication equipment often densely arranges multiple optical modules. The space limitation causes the heat sink to be unable to get enough air flow, which not only increases the temperature, but also affects the overall stability of the system. In the heat dissipation management of optical modules, thermal interface materials (TIMs) play a vital role. Thermal interface materials can fill the tiny gap between the heat generating component and the heat sink, significantly improve the thermal conductivity, reduce the thermal resistance, and thus enhance the heat transfer efficiency. In addition, thermal interface materials can also maintain stable physical properties in various thermal cycles, thereby preventing failure caused by thermal fatigue. Therefore, thermal interface materials have become the most potential material for solving the heat dissipation problem of optical modules.
[0003] Thixotropic stress-yield fluids exhibit unique internal structural properties, which enable them to have solid characteristics under small stress conditions. When the applied stress exceeds its yield point, this internal structure will be destroyed, the fluidity will be enhanced, and it will show a low-viscosity liquid state. Under low shear rates and static conditions, the internal state of these fluids will gradually recover, making them show solid-like properties again. Due to the special properties of thixotropic thermal conductive silicone composites, their applications in electronic devices and robots have also been explored, such as optical modules, wearable electronic devices, stretchable optical fibers, adhesives, and soft robots. During the operation of electronic devices, considerable heat is generated. Due to the inconsistent thermal expansion coefficients between the heat sink and the electronic device and the large thermal resistance of the contact surface, the effectiveness of the heat sink is significantly affected, which may greatly shorten the service life of the electronic device. Therefore, it is particularly important to achieve effective thermal management.
[0004] Due to its excellent thixotropy, stress-yielding fluid can effectively fill the gap between electronic devices and heat sinks, ensuring that the equipment works within the appropriate temperature range. However, existing thermally conductive silicone composite materials have problems such as poor thermal conductivity, stability, or oil permeability. Summary of the invention
[0005] In view of this, the present application provides a thermally conductive silicone composite material and an electronic device, aiming to improve the technical problem of unsatisfactory thermal conductivity or oil permeability of existing silicone heat dissipation materials.
[0006] In a first aspect, an embodiment of the present application provides a thermally conductive organic silicon composite material, comprising, by weight: 2 to 10 parts of silicone resin and 90 to 98 parts of thermally conductive filler;
[0007] The silicone resin includes a brush polymer.
[0008] Optionally, the mass ratio of the thermally conductive filler to the thermally conductive silicone composite material is 92% to 98%.
[0009] Optionally, the brush polymer is prepared by reacting side chain hydrogen-containing polydimethylsiloxane and single-end vinyl polydimethylsiloxane.
[0010] The molar number of active hydrogen in the single-end vinyl polydimethylsiloxane is M1, the molar number of vinyl in the side chain hydrogen-containing polydimethylsiloxane is M2, and M1 / M2 is 0.1 to 0.8.
[0011] Optionally, M1 / M2 is 0.3 to 0.5.
[0012] Optionally, the thermally conductive filler includes a first filler, a second filler and a third filler. The particle size of the first filler is 70 μm to 90 μm, the particle size of the second filler is 8 μm to 25 μm, and the particle size of the third filler is 0.1 μm to 6 μm. Calculated by mass ratio, the first filler: the second filler: the third filler is (7 to 9): (3.5 to 5.5): (3 to 5).
[0013] Optionally, the second filler includes a first sub-filler and a second sub-filler, and the particle size of the second sub-filler is smaller than that of the first sub-filler; and / or
[0014] The third filler includes a third sub-filler and a fourth sub-filler, and a particle size of the fourth sub-filler is smaller than a particle size of the third sub-filler.
[0015] Optionally, the particle size of the first sub-filler is 15 μm to 25 μm; and / or
[0016] The average particle size of the second sub-filler is 8 μm to 15 μm; and / or
[0017] The average particle size of the third sub-filler is 2 μm to 6 μm; and / or
[0018] The average particle size of the fourth sub-filler is 0.1 μm to 0.8 μm.
[0019] Optionally, the particle size of the first sub-filler is 15 μm to 25 μm, the average particle size of the second sub-filler is 8 μm to 15 μm, and the mass ratio of the first sub-filler to the second sub-filler is (2 to 3): (1.5 to 2.5); and / or
[0020] The average particle size of the third sub-filler is 2 μm to 6 μm, the average particle size of the fourth sub-filler is 0.1 μm to 0.8 μm, and the mass ratio of the third sub-filler to the fourth sub-filler is (1.5 to 2.5): (1.5 to 2.5) 。
[0021] Optionally, the first filler, the second filler and the third filler are spherical fillers; and / or
[0022] The first filler, the second filler and the third filler are independently selected from at least one of aluminum oxide, aluminum nitride, zinc oxide, boron nitride and diamond; and / or
[0023] The thermally conductive filler also includes flake filler.
[0024] Optionally, the particle size of the flaky filler is 10 μm to 20 μm; and / or
[0025] In terms of mass fractions, the first filler: the second filler: the third filler: the sheet material is (7-9): (3.5-5.5): (3-5): (0.1-2); and / or
[0026] The first filler, the second filler and the third filler are all spherical aluminum oxide;
[0027] The flake filler includes flake boron carbide.
[0028] A second aspect of the present application provides an electronic device, which includes an optical module and the thermally conductive organic silicon composite material. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0031] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0032] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0033] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0034] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0035] In the prior art, various types of optical modules have been widely developed and applied, including SFP, SFP+, QSFP, etc. However, existing optical modules still have some obvious problems in terms of transmission rate, power consumption, size and heat dissipation performance. In particular, the surge in heat causes great challenges to the performance and application of optical modules. The design of traditional heat sinks often cannot fully cope with the rapidly rising temperature. In high-power optical modules, the heat exchange capacity of the heat sink cannot quickly discharge the generated heat, resulting in a continuous rise in module temperature. Secondly, in order to achieve high integration, modern communication equipment often densely arranges multiple optical modules. The space limitation causes the heat sink to be unable to get enough air flow, which not only increases the temperature, but also affects the overall stability of the system. In the heat dissipation management of optical modules, thermal interface materials (TIMs) play a vital role. Thermal interface materials can fill the tiny gap between the heat generating component and the heat sink, significantly improve the thermal conductivity, reduce the thermal resistance, and thus enhance the heat transfer efficiency. In addition, thermal interface materials can also maintain stable physical properties in various thermal cycles, thereby preventing failure caused by thermal fatigue. Therefore, thermal interface materials have become the most potential material for solving the heat dissipation problem of optical modules.
[0036] Thixotropic stress-yield fluids exhibit unique internal structural properties, which enable them to have solid characteristics under small stress conditions. When the applied stress exceeds its yield point, this internal structure will be destroyed, the fluidity will be enhanced, and it will show a low-viscosity liquid state. Under low shear rates and static conditions, the internal state of these fluids will gradually recover, making them show solid-like properties again. Due to the special properties of thixotropic thermal conductive silicone composites, their applications in electronic devices and robots have also been explored, such as optical modules, wearable electronic devices, stretchable optical fibers, adhesives, and soft robots. During the operation of electronic devices, considerable heat is generated. Due to the inconsistent thermal expansion coefficients between the heat sink and the electronic device and the large thermal resistance of the contact surface, the effectiveness of the heat sink is significantly affected, which may greatly shorten the service life of the electronic device. Therefore, it is particularly important to achieve effective thermal management.
[0037] Thixotropic stress yielding fluid can effectively fill the gap between electronic devices and heat sinks due to its excellent thixotropy, ensuring that the equipment works within the appropriate temperature range. However, existing thermally conductive silicone composite materials have problems such as poor thermal conductivity, stability, or oil permeability.
[0038] In view of this, an embodiment of the present application provides a thermally conductive silicone composite material (also called silicone heat dissipation material), which includes, by mass: 2 to 10 parts of silicone resin and 90 to 98 parts of thermally conductive filler; the silicone resin includes a brush polymer.
[0039] In the embodiments of the present application, a brush-coated polymer is added to the silicone resin matrix, thereby increasing the yield stress and thermal conductivity of the thermally conductive organic silicon composite material in the present application and reducing its oil permeability.
[0040] Exemplarily, the brush polymer is prepared by reacting a single-terminal vinyl polydimethylsiloxane with a side chain hydrogen-containing polydimethylsiloxane. Of course, in other embodiments of the present application, the brush polymer can also be prepared by reacting a polydimethylsiloxane containing other first active functional groups on the side chain with a polydimethylsiloxane terminated with other second active functional groups, which is not limited here.
[0041] In some embodiments of the present application, the number of moles of vinyl in the single-end vinyl polydimethylsiloxane is M1, the number of moles of active hydrogen in the side chain hydrogen-containing polydimethylsiloxane is M2, and M1 / M2 is 0.1 to 0.8. Further, M1 / M2 is 0.3 to 0.5. This is conducive to further improving the thermal conductivity and yield stress of the organic silicon heat dissipation material in the present application, and reducing the oil permeability of the organic silicon heat dissipation material in the present application.
[0042] In some embodiments of the present application, the thermally conductive filler includes a first filler, a second filler and a third filler, the average particle size of the first filler is 70 μm to 90 μm, the average particle size of the second filler is 8 μm to 25 μm, and the average particle size of the third filler is 0.1 μm to 6 μm, and the mass ratio of the first filler: the second filler: the third filler is (7 to 9): (3.5 to 5.5): (3 to 5). The organic silicon heat dissipation material prepared in the embodiments of the present application has high thermal conductivity and yield stress, and has low mobility, so that the organic silicon heat dissipation material in the present application has high thermal conductivity and stability, and has low oil permeability.
[0043] It should be noted that, unless otherwise specified, the particle size in this application refers to the average particle size or median particle size (eg D50).
[0044] Illustratively, the mass fraction of silicone resin in the organic silicon heat dissipation material in the present application is 2, 3, 4, 5, 6, 7, 8, 9, 10 and values between any two of the above values.
[0045] Illustratively, the mass fraction of the thermally conductive filler in the silicone heat dissipation material in the present application is 90, 91, 92, 93, 94, 95, 96, 97, 98 and values between any two of the above values.
[0046] Exemplarily, the average particle size of the first filler in the silicone heat dissipation material in the present application is 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 79μm, 80μm, 81μm, 82μm, 83μm, 84μm, 85μm, 86μm, 87μm, 88μm, 89μm, 90μm and values between any two of the above values.
[0047] Exemplarily, the average particle size of the second filler in the silicone heat dissipation material in the present application is 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm and values between any two of the above values.
[0048] Illustratively, the average particle size of the third filler in the silicone heat dissipation material in the present application is 0.1μm, 0.2μm, 0.5μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm and values between any two of the above values.
[0049] Exemplarily, the mass ratio of the first filler: the second filler: the third filler is 7:3.5:3, 7:4:3, 7:4.5:3, 7:5:3, 7:5.5:3, 7:3.5:3.5, 7:3.5:4, 7:3.5:4.5, 7:3.5:5, 7:4:3.5, 7:4:4, 7:4:4.5, 7:4:5, 7:4.5:3.5, 7:4.5:4, 7:4.5:4.5, 7:4.5:4.5, 7:4.5:5. .5:5, 7:5:3.5, 7:5:4, 7:5:4.5, 7:5:5, 7:5.5:3.5, 7:5.5:4, 7:5.5:4.5, 7:5.5:5, 8:3.5:3, 8:4:3, 8:4.5:3, 8:5:3, 8:5.5:3, 8:3.5:3.5, 8:3.5:4, 8:3.5:4.5, 8:3.5:5, 8:4:3.5, 8:4:4, 8:4:4. 5, 8:4:5, 8:4.5:3.5, 8:4.5:4, 8:4.5:4.5, 8:4.5:5, 8:5:3.5, 8:5:4, 8:5:4.5, 8:5:5, 8:5.5:3.5, 8:5.5:4, 8:5.5:4.5, 8:5.5:5, 9:3.5:3, 9:4:3, 9:4.5:3, 9:5:3, 9:5.5:3, 9:3.5:3.5, 9:3.5:4 , 9:3.5:4.5, 9:3.5:5, 9:4:3.5, 9:4:4, 9:4:4.5, 9:4:5, 9:4.5:3.5, 9:4.5:4, 9:4.5:4.5, 9:4.5:5, 9:5:3.5, 9:5:4, 9:5:4.5, 9:5:5, 9:5.5:3.5, 9:5.5:4, 9:5.5:4.5, 9:5.5:5 and values between any two of the above ratios.
[0050] The embodiment of the present application adds a first filler, a second filler and a third filler of specific particle sizes to the silicone heat dissipation material, and controls the first filler: the second filler: the third filler to satisfy (7-9): (3.5-5.5): (3-5), so that the silicone heat dissipation material in the present application has a higher thermal conductivity and better fluidity.
[0051] Optionally, the second filler includes a first sub-filler and a second sub-filler, and the particle size of the second sub-filler is smaller than that of the first sub-filler. Furthermore, the average particle size of the first sub-filler is 15 μm to 25 μm, the average particle size of the second sub-filler is 8 μm to 15 μm, and the mass ratio of the first sub-filler to the second sub-filler is (2 to 3): (1.5 to 2.5). In this way, the thermal conductivity of the silicone heat dissipation material in the present application is further improved.
[0052] Optionally, the third filler includes a third sub-filler and a fourth sub-filler, and the particle size of the fourth sub-filler is smaller than the particle size of the third sub-filler. Furthermore, the average particle size of the third sub-filler is 2μm to 6μm, the average particle size of the fourth sub-filler is 0.1μm to 0.8μm, and the mass ratio of the third sub-filler to the fourth sub-filler is (1.5 to 2.5): (1.5 to 2.5). Furthermore, the average particle size of the third sub-filler is 4μm to 6μm, and the average particle size of the fourth sub-filler is 0.1μm to 0.4μm. In this way, it is beneficial to further improve the thermal conductivity of the silicone heat dissipation material in the present application.
[0053] Optionally, the second filler includes a first sub-filler and a second sub-filler, and the third filler includes a third sub-filler and a fourth sub-filler. Calculated by mass, the first filler: the first sub-filler: the second sub-filler: the third sub-filler: the fourth sub-filler is (7.5-8.5): (2-3): (1.5-2.5): (1.5-2.5): (1.5-2.5). This is conducive to further improving the thermal conductivity of the silicone heat dissipation material in the present application.
[0054] In some embodiments of the present application, the first filler, the second filler and the third filler are all spherical fillers. This is beneficial to increase the mass percentage of the thermally conductive filler in the organic silicon heat dissipation material in the present application, to further improve the yield stress and thermal conductivity of the organic silicon heat dissipation material in the application, and to reduce the oil permeability of the organic silicon heat dissipation material in the application.
[0055] In some embodiments of the present application, the first filler, the second filler and the third filler are all spherical fillers, and the thermally conductive filler also includes a flaky filler. Furthermore, the average particle size of the flaky filler is 10 μm to 20 μm, and in terms of mass fraction, the first filler: the second filler: the third filler: the flaky filler is (7 to 9): (3.5 to 5.5): (3 to 5): (0.1 to 2). In this embodiment, by adding a flaky filler of a specific particle size to the silicone heat dissipation material, and by controlling the first filler: the second filler: the third filler: the flaky filler to be (7 to 9): (3.5 to 5.5): (3 to 5): (0.1 to 2), the yield stress and thermal conductivity of the silicone heat dissipation material in the present application are further improved, and the oil permeability is further reduced.
[0056] Exemplarily, the average particle size of the flaky filler is 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, and values between any two of the above values.
[0057] In some embodiments of the present application, by weight, the first filler: the second filler: the third filler: the flaky filler is (7-9): (3.5-5.5): (3-5): (0.4-1.7). Further, the first filler: the second filler: the third filler: the flaky filler is (7-9): (3.5-5.5): (3-5): (0.4-0.9). It is worth mentioning that those skilled in the art can generally expect that as the proportion of thermally conductive fillers in the resin matrix increases, its thermal conductivity will also increase. However, the inventors have found through experiments that in the present application, as the proportion of flaky fillers in the organosilicon heat dissipation material increases, the yield stress of the organosilicon heat dissipation material will gradually increase, and the mobility of the organosilicon heat dissipation material will gradually decrease, but the thermal conductivity of the organosilicon heat dissipation material shows a trend of first increasing and then decreasing. In other words, after the addition amount of flaky fillers in the organosilicon heat dissipation material in the present application reaches a certain value, its thermal conductivity will begin to decrease. In this embodiment, the mass ratio of the flaky filler is further controlled to be 0.4 to 0.9, so that the organic silicon heat dissipation material in the present application has a higher thermal conductivity, lower mobility and higher yield stress.
[0058] In some embodiments of the present application, the first filler, the second filler, the third filler and the flaky filler are independently selected from one or more of silicon dioxide, aluminum hydroxide, magnesium hydroxide, aluminum oxide, magnesium oxide, titanium dioxide, talc, mica powder, clay, barium sulfate, barium titanate, calcium carbonate, aluminum silicate and calcium silicate.
[0059] Exemplarily, the first filler, the first sub-filler, the second sub-filler, the third sub-filler, and the fourth sub-filler are all spherical aluminum oxide, and the flake filler is flake boron nitride.
[0060] In some embodiments of the present application, the thermally conductive filler consists of the first filler, the first sub-filler, the second sub-filler, the third sub-filler, the fourth sub-filler and the flake boron nitride.
[0061] In some embodiments of the present application, the silicone resin is selected from at least one of side chain hydrogen-containing polydimethylsiloxane, side chain hydrogen-containing polydimethylsiloxane, single-end vinyl polydimethylsiloxane, and single-end vinyl-terminated polydimethylsiloxane.
[0062] In some embodiments of the present application, the mass ratio of silicone resin to thermal conductive filler is (6 to 7.5): (92.5 to 94).
[0063] In some embodiments of the present application, the viscosity of the silicone resin is 10-2500 mPa·s. For example, the viscosity of the silicone resin is 10 mPa·s, 50 mPa·s, 100 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s, 500 mPa·s, 600 mPa·s, 700 mPa·s, 800 mPa·s, 900 mPa·s, 1000 mPa·s, 1100 mPa·s, 1200 mPa·s, 1 s, 300mPa·s, 1400mPa·s, 1500mPa·s, 1600mPa·s, 1700mPa·s, 1800mPa·s, 1900mPa·s, 2000mPa·s, 2100mPa·s, 2200mPa·s, 2300mPa·s, 2400mPa·s, 2500mPa·s and values between any two of the above values. It should be noted that, unless otherwise specified, the viscosity in this application refers to the viscosity at room temperature (25°C).
[0064] In some embodiments of the present application, the silicone resin includes a side chain hydrogen-containing polydimethylsiloxane and a single-end vinyl polydimethylsiloxane, the mass fraction of the side chain hydrogen-containing polydimethylsiloxane is 0.1 to 8.5 parts, and the mass fraction of the single-end vinyl polydimethylsiloxane is 0.1 to 8.5 parts; the viscosity of the side chain hydrogen-containing polydimethylsiloxane is 10-2500mPa·s, and the viscosity of the single-end vinyl polydimethylsiloxane is 10-2500mPa·s. The silicone resin in this embodiment includes a side chain hydrogen-containing polydimethylsiloxane and a single-end vinyl polydimethylsiloxane, so that the side chain hydrogen-containing polydimethylsiloxane and the single-end vinyl polydimethylsiloxane can be cross-linked to form a long-chain brush polymer, which is beneficial to further improve the thermal conductivity and yield stress of the silicone heat dissipation material in the present application, and reduce the oil permeability of the silicone heat dissipation material in the present application.
[0065] Further, the content of vinyl in the side chain hydrogen-containing polydimethylsiloxane is 0.1%-3.0%. Exemplarily, the content of vinyl in the side chain hydrogen-containing polydimethylsiloxane is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% and values between any two of the above values.
[0066] Furthermore, the hydrogen content of the single-end vinyl polydimethylsiloxane is 0.05%-1.2%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% and any value between the above two values.
[0067] The organic silicon heat dissipation material in the present application is further described below in conjunction with specific embodiments and experimental tests.
[0068] Example 1
[0069] First, spherical alumina powders with particle sizes of 80um, 20um, 10um, 5um, and 0.2um were weighed according to the ratio of 8:2.5:2:2:2. The weighed alumina powders were rotated in a high-speed mixer at 800r / min for 1 minute, then at 1200r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain thermal conductive filler for use.
[0070] Under a protective atmosphere, 20g of side chain hydrogenated polydimethylsiloxane and 9.06g of single-end vinyl polydimethylsiloxane were mixed. The viscosity of the side chain hydrogenated polydimethylsiloxane was 50mPa·s, the hydrogen content was 0.17%, and the molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034mmol. The viscosity of the single-end vinyl polydimethylsiloxane was 50mPa·s, the vinyl content was 0.075%, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068mmol. Then, 0.01g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the reaction was carried out at 120°C for 4h to obtain a long-chain branched brush polymer for standby use.
[0071] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 1).
[0072] Example 2
[0073] First, spherical alumina powders with particle sizes of 80um, 20um, 10um, 5um, and 0.2um were weighed according to the ratio of 8:2.5:2:2:2. The weighed alumina powders were rotated in a high-speed mixer at 800r / min for 1 minute, then at 1200r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain thermal conductive filler for use.
[0074] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 18.12 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. Then, 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for use.
[0075] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 2).
[0076] Example 3
[0077] First, spherical alumina powders with particle sizes of 80um, 20um, 10um, 5um, and 0.2um were weighed according to the ratio of 8:2.5:2:2:2. The weighed alumina powders were rotated in a high-speed mixer at 800r / min for 1 minute, then at 1200r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain thermal conductive filler for use.
[0078] Under protective atmosphere, 20g of side chain hydrogenated polydimethylsiloxane with a viscosity of 50mPa·s and a hydrogen content of 0.17% and 27.2g of single-end vinyl polydimethylsiloxane with a viscosity of 50mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068mmol. Then, 0.01g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4h to obtain a long-chain branched brush polymer for standby use.
[0079] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 3).
[0080] Example 4
[0081] First, spherical alumina powder with particle sizes of 80um, 20um, 10um, 5um, and 0.2um and flaky boron nitride (particle size of 15um) are weighed according to 8:2.5:2:2:2:0.42. The weighed alumina powder and flaky boron nitride are rotated at 800r / min in a high-speed mixer for 1 minute, then at 1200r / min for 30 seconds, and put into a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0082] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 18.12 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. Then, 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for use.
[0083] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 4).
[0084] Example 5
[0085] First, spherical alumina powder with particle sizes of 80um, 20um, 10um, 5um, and 0.2um and flaky boron nitride (particle size of 15um) are weighed according to 8:2.5:2:2:2:0.82. The weighed alumina powder and flaky boron nitride are rotated at 800r / min in a high-speed mixer for 1 minute, then at 1200r / min for 30 seconds, and put into a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0086] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 18.12 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. Then, 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for use.
[0087] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 5).
[0088] Example 6
[0089] First, spherical alumina powder with particle sizes of 80um, 20um, 10um, 5um, and 0.2um and flaky boron nitride (particle size of 15um) are weighed according to 8:2.5:2:2:2:1.68. The weighed alumina powder and flaky boron nitride are rotated in a high-speed mixer at 800r / min for 1 minute, then at 1200r / min for 30 seconds, and put into a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0090] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 18.12 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for standby use.
[0091] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 6).
[0092] Example 7
[0093] First, spherical alumina powder with a particle size of 80 μm was rotated in a high-speed mixer at 800 r / min for 1 minute, then rotated at 1200 r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0094] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 9.06 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for standby use.
[0095] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 7).
[0096] Example 8
[0097] First, spherical alumina powders with particle sizes of 80um, 20um, 10um, 5um, and 0.2um were weighed according to the ratio of 8:2.5:2:2:2. The weighed alumina powders were rotated in a high-speed mixer at 800r / min for 1 minute, then at 1200r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain thermal conductive filler for use.
[0098] Under a protective atmosphere, 20 g of a side chain hydrogenated polydimethylsiloxane with a viscosity of 50 mPa·s and a hydrogen content of 0.17% and 18.12 g of a single-end vinyl polydimethylsiloxane with a viscosity of 50 mPa·s and a vinyl content of 0.075% were mixed. The molar number of active hydrogen in the side chain hydrogenated polydimethylsiloxane was 0.034 mmol, and the molar number of vinyl in the single-end vinyl polydimethylsiloxane was 0.0068 mmol. Then, 0.01 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was reacted at 120°C for 4 hours to obtain a long-chain branched brush polymer for use.
[0099] Subsequently, 94% by mass of thermal conductive filler and 6% by mass of long-chain branched brush polymer were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (ie, test sample 8).
[0100] Comparative Example 1
[0101] First, spherical alumina powder with a particle size of 80 μm was rotated in a high-speed mixer at 800 r / min for 1 minute, then rotated at 1200 r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0102] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of single-end vinyl polydimethylsiloxane were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (also known as comparison sample 1).
[0103] Comparative Example 2
[0104] First, spherical alumina powder with a particle size of 20 μm was rotated in a high-speed mixer at 800 r / min for 1 minute, then at 1200 r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0105] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of single-end vinyl polydimethylsiloxane were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (also known as comparison sample 2).
[0106] Comparative Example 3
[0107] First, spherical alumina powder with a particle size of 5 μm was rotated in a high-speed mixer at 800 r / min for 1 minute, then rotated at 1200 r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0108] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of single-end vinyl polydimethylsiloxane were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (also known as comparison sample 3).
[0109] Comparative Example 4
[0110] First, the flake boron carbide powder with a particle size of 15 μm was rotated in a high-speed mixer at 800 r / min for 1 minute, and then rotated at 1200 r / min for 30 seconds, and placed in a drying oven to dry the moisture to obtain a thermal conductive filler for use.
[0111] Subsequently, 93% by mass of thermal conductive filler and 7% by mass of single-end vinyl polydimethylsiloxane were weighed and added into a high-speed mixer and stirred at 800 r / min for 1 minute, then at 1200 r / min for 1 minute, and then at 1500 r / min for 40 seconds to obtain a silicone heat dissipation material (also known as comparison sample 4).
[0112] Comparative Example 5
[0113] The difference between Comparative Example 5 and Example 2 is that the mass fraction of filler: the ratio of filler to matrix is 89:11 (i.e., Comparative Sample 5)
[0114] Experimental testing
[0115] (1) Thermal conductivity test:
[0116] The thermal conductivity of the material was evaluated according to ASTM D5470. The fluid was evenly applied to the mold (25.4 mm × 25.4 mm × 3 mm) and tested using the LW-9389TIM thermal resistance and conductivity meter at 80°C and 10 psi.
[0117] (2) Yield stress test:
[0118] Yield stress test: The yield stress of the composite fluid is measured at room temperature using a PP25 plate test system using a stress-strain curve, where the shear stress increases logarithmically. At low shear stress and small strain, a straight line is fitted in the elastic range, and then at high shear stress and large strain, another straight line is fitted in the flow range, and finally the intersection of the two straight lines is used as the yield point.
[0119] (3) Mobility test:
[0120] Weigh the sample to obtain its initial weight m1, and place filter paper on both sides of the sample (the sample stacking structure from bottom to top is: tin foil, 2 qualitative filter papers, 1 quantitative filter paper, sample, 1 quantitative filter paper, 2 qualitative filter papers, aluminum foil). Place the prepared sample on an aluminum plate in a 125°C constant temperature forced air drying oven, apply a 10N weight on top of the sample, bake for 72 hours, take it out and put it in a dryer, wait until it reaches room temperature, weigh the sample and filter paper m2, wipe off the residual sample on the filter paper, weigh the filter paper m3, and calculate its weight loss rate.
[0121] (4) Thixotropy test:
[0122] The Anton Paar rheometer PP25 flat plate test system was used at room temperature and the oscillatory shear three-stage method was used for measurement. First, a small amplitude shear (0.1%) was applied to simulate the static state of the composite fluid, then a large amplitude shear (10%) was applied to make the composite fluid undergo a solid-liquid transition, and finally a small amplitude shear (0.1%) was applied to wait for the composite fluid structure to recover. The structural recovery rate of the yield stress composite fluid is defined as the ratio of the storage modulus in the structural recovery stage to the storage modulus in the initial stage.
[0123] The yield stress, thermal conductivity and mobility of the samples prepared in the experimental example were tested, and the test results are shown in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] It can be seen from Table 1 that the test results of Examples 1 to 8 and Comparative Example 1 show that adding a brush polymer to the thermally conductive silicone composite material is beneficial to improving the yield stress and thermal conductivity of the thermally conductive silicone composite material and reducing its oil permeability.
[0128] From the test results of Examples 1 to 6, Examples 8 and 7 and Comparative Examples 1 to 3, it can be seen that the compounding of thermally conductive fillers with specific particle sizes in the embodiments of the present application is beneficial to improving the yield stress and thermal conductivity of the silicone heat dissipation material in the present application, and reducing its oil permeability.
[0129] It can be seen from the test results of Example 1 and Comparative Examples 1 to 3 that the compounding of thermally conductive fillers of specific particle sizes in the embodiments of the present application has a synergistic effect in improving yield stress, improving thermal conductivity and reducing oil permeability.
[0130] It can be seen from Examples 2, 4 to 6 that adding a certain amount of flaky boron nitride can significantly increase the yield stress and thermal conductivity of the silicone heat dissipation material in the present application, and also has a certain effect on reducing the mobility. As the proportion of flaky fillers in the silicone heat dissipation material increases, the yield stress of the silicone heat dissipation material will gradually increase, and the mobility of the silicone heat dissipation material will gradually decrease, but the thermal conductivity of the silicone heat dissipation material shows a trend of first increasing and then decreasing. In other words, after the amount of flaky fillers added in the silicone heat dissipation material in the present application reaches a certain value, its thermal conductivity will begin to decrease. In this embodiment, by further controlling the mass ratio of the flaky fillers to 0.4 to 0.9, the silicone heat dissipation material in the present application has a higher thermal conductivity, while having a lower mobility and a higher yield stress.
[0131] The possible reason is that any filler surface in the thermal interface material will adsorb a layer of polymer matrix, which has a worse mobility than the polymer far away from the filler surface, while the flake boron nitride has a larger surface area to volume ratio, so the surface can adsorb more polymer matrix, thereby further reducing the mobility. The flake boron nitride added at the same time will be embedded in the gaps of the spherical filler, thereby increasing the structural strength of the thermal interface material cluster, thus further increasing the yield stress. Flake boron nitride is anisotropic in thermal conductivity, with better thermal conductivity along the direction of the flake and reduced thermal conductivity in other directions. Filling in a small amount of flake boron nitride will make the cluster structure more compact, which is conducive to phonon transmission, thereby increasing thermal conductivity. However, when more boron nitride is filled, the direction of the boron nitride filled in the thermal interface material is random, so the thermal conductivity of the thermal interface material will decrease.
[0132] From the comparison of Examples 1 to 6, it can be seen that the resin matrix includes a long-chain branched brush polymer, and when M1 / M2 is larger, the number of branches in the obtained long-chain branched brush polymer is larger, which can further improve the yield stress and thermal conductivity of the silicone heat dissipation material in the present application, and reduce its oil permeability. When the ratio of M1 / M2 is large (for example, M1 / M2 is close to 0.6), its viscosity is large, and the dispensing shape and coverage ability of the obtained thermally conductive yield stress fluid (i.e., silicone heat dissipation material) are reduced.
[0133] It can be seen from the test results of Examples 1 to 6 and Example 7 that when the second filler includes a first sub-filler and a second sub-filler, the average particle size of the first sub-filler is 15μm~25μm, the average particle size of the second sub-filler is 8μm~15μm, the third filler includes a third sub-filler and a fourth sub-filler, the average particle size of the third sub-filler is 2μm~6μm, and the average particle size of the fourth sub-filler is 0.1μm~0.8μm, and the first filler: the first sub-filler: the second sub-filler: the third sub-filler: the fourth sub-filler is (7.5~8.5): (2~3): (1.5~2.5): (1.5~2.5): (1.5~2.5), the yield stress and thermal conductivity of the silicone heat dissipation material in the present application can be further improved, and its oil permeability can be reduced.
[0134] It can be seen from the test results of Examples 4 to 6 and Comparative Examples 1 to 4 that the grading of aluminum oxide with different particle sizes and flaky boron nitride in the embodiments of the present application have a synergistic effect in improving the yield stress and thermal conductivity of the silicone heat dissipation material in the present application and reducing its oil permeability.
[0135] It can be seen from the test results of Example 2 and Comparative Example 5 that if the proportion of thermally conductive filler in the thermally conductive material is low (its proportion in the thermally conductive filler is less than 89 parts), its mobility is high, its yield stress is small, and its thermal conductivity is also low, which is not conducive to obtaining a yield stress fluid with high thermal conductivity, low oil permeability and good stability.
[0136] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A thermally conductive silicone composite material, characterized in that: Calculated by weight, it includes: 2 to 10 parts of silicone resin and 90 to 98 parts of thermal conductive filler; The silicone resin includes a brush polymer.
2. The thermally conductive organic silicon composite material according to claim 1, characterized in that: The brush-like polymer is prepared by reacting a side chain hydrogen-containing polydimethylsiloxane with a single-end vinyl polydimethylsiloxane; and / or The mass ratio of the thermally conductive filler to the thermally conductive organic silicon composite material is 92% to 98%.
3. The thermally conductive organic silicon composite material according to claim 2, characterized in that: The molar number of active hydrogen in the single-end vinyl polydimethylsiloxane is M1, the molar number of vinyl in the side chain hydrogen-containing polydimethylsiloxane is M2, and M1 / M2 is 0.1 to 0.
8.
4. The thermally conductive organic silicon composite material according to claim 3, characterized in that: M1 / M2 is 0.3 to 0.
5.
5. The thermally conductive organic silicon composite material according to any one of claims 1 to 4, characterized in that: The thermally conductive filler includes a first filler, a second filler and a third filler. The particle size of the first filler is 70 μm to 90 μm, the particle size of the second filler is 8 μm to 25 μm, and the particle size of the third filler is 0.1 μm to 6 μm. Calculated by mass ratio, the first filler: the second filler: the third filler is (7 to 9): (3.5 to 5.5): (3 to 5).
6. The thermally conductive organic silicon composite material according to claim 5, characterized in that: The second filler includes a first sub-filler and a second sub-filler, and the particle size of the second sub-filler is smaller than the particle size of the first sub-filler; and / or The third filler includes a third sub-filler and a fourth sub-filler, and a particle size of the fourth sub-filler is smaller than a particle size of the third sub-filler.
7. The thermally conductive organic silicon composite material according to claim 6, characterized in that: The particle size of the first sub-filler is 15 μm to 25 μm; and / or The average particle size of the second sub-filler is 8 μm to 15 μm; and / or The average particle size of the third sub-filler is 2 μm to 6 μm; and / or The average particle size of the fourth sub-filler is 0.1 μm to 0.8 μm.
8. The thermally conductive organic silicon composite material according to claim 6, characterized in that: The particle size of the first sub-filler is 15 μm to 25 μm, the average particle size of the second sub-filler is 8 μm to 15 μm, and the mass ratio of the first sub-filler to the second sub-filler is (2 to 3): (1.5 to 2.5); and / or The average particle size of the third sub-filler is 2 μm to 6 μm, the average particle size of the fourth sub-filler is 0.1 μm to 0.8 μm, and the mass ratio of the third sub-filler to the fourth sub-filler is (1.5 to 2.5): (1.5 to 2.5) 。 9. The thermally conductive organic silicon composite material according to claim 5, characterized in that: The first filler, the second filler and the third filler are spherical fillers; and / or The first filler, the second filler and the third filler are independently selected from at least one of aluminum oxide, aluminum nitride, zinc oxide, boron nitride and diamond; and / or The thermally conductive filler also includes flake filler.
10. The thermally conductive organic silicon composite material according to claim 9, characterized in that: The particle size of the flaky filler is 10 μm to 20 μm; and / or In terms of mass fractions, the first filler: the second filler: the third filler: the flaky filler is (7-9): (3.5-5.5): (3-5): (0.1-2); and / or The first filler, the second filler and the third filler are all spherical aluminum oxide; The flake filler includes flake boron carbide.
11. An electronic device, characterized in that: The electronic device comprises an optical module and the thermally conductive organic silicon composite material according to any one of claims 1 to 10.
Citation Information
Patent Citations
High-flexibility low-seepage heat-conducting silica gel and preparation method thereof
CN111286200A
Multi-branched chain polysiloxane, preparation method thereof and heat-conducting silica gel
CN114539533A
Heat-conducting organic silicon composite material for chip packaging and preparation method of heat-conducting organic silicon composite material
CN117701234A
Gecko-claw-imitating composite thermal interface material and preparation method therefor
WO2024036611A1